2021
DOI: 10.7759/cureus.15939
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Efficiency of Fusion Robotics™ Versus Mazor-X™ in Single-Level Lumbar Pedicle Screw Placement

Abstract: Introduction There has been a surge in robot utilization in spine surgery over the past five years with the rapid development of new spine robotic platforms. This study aimed to compare a new robotic spine platform from Fusion Robotics TM (Fusion Robotics, Helena, MT) with the widely used Mazor-X TM Stealth Edition robotic platform (Medtronic, Dublin, Ireland) in terms of workflow and lumbar pedicle screw placement accuracy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A previous study compared the workflow efficiency of inserting 4 pedicle screws into 2 adjacent lumbar vertebrae using this new robotic 3D navigation system (formerly Fusion Robotics) with the Mazor-X Stealth Edition spine robot (Medtronic, Dublin, Ireland). 5 The study showed that, while both systems were accurate, the new robotic navigation system had significantly better workflow efficiency measurements (total procedure time, system setup time, and screw planning to in-position time) than did the Mazor-X Stealth Edition (Figure 3 and Table ). 5…”
Section: Workflow Efficiencymentioning
confidence: 92%
See 2 more Smart Citations
“…A previous study compared the workflow efficiency of inserting 4 pedicle screws into 2 adjacent lumbar vertebrae using this new robotic 3D navigation system (formerly Fusion Robotics) with the Mazor-X Stealth Edition spine robot (Medtronic, Dublin, Ireland). 5 The study showed that, while both systems were accurate, the new robotic navigation system had significantly better workflow efficiency measurements (total procedure time, system setup time, and screw planning to in-position time) than did the Mazor-X Stealth Edition (Figure 3 and Table ). 5…”
Section: Workflow Efficiencymentioning
confidence: 92%
“…5 The study showed that, while both systems were accurate, the new robotic navigation system had significantly better workflow efficiency measurements (total procedure time, system setup time, and screw planning to in-position time) than did the Mazor-X Stealth Edition (Figure 3 and Table ). 5…”
Section: Workflow Efficiencymentioning
confidence: 92%
See 1 more Smart Citation
“…8 For the computer-aided planning approaches, only single vertebral pedicle screw path planning methods were reported. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Wicker et al relies on the geometric constraints of the single vertebral structures, 18 which is further improved by the introduction of safety boundary constraints. 19 More development depends on the correlations between the vertebral bone mineral density (BMD) and the screw placement trajectories from different angles for preoperative screw trajectory planning.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Recently, several literatures have reported that the 3D preoperative planning approaches can find the optimal screw trajectory through the bone mechanics or BMD characteristics derived from CT images. [24][25][26][27][28][29] Some researchers also optimize the screw trajectory according to the CT image and the geometric characteristics of the vertebral body, for example, by constructing multi-angle projections and marking the avoidance area on the projection plane to find the optimal screw trajectories. 30 Knez et al developed a technology to parameterize the vertebral body and pedicle into mathematical models and register these models to the patient's CT image.…”
Section: Introductionmentioning
confidence: 99%